Analisis Percepatan Gravitasi Pada Gerak Jatuh Bebas Menggunakan Aplikasi Video Tracker - Nggolaon, Delpina; Silahooy, Stevi (Physikos: Journal of Physics and Physics Education, 2023)
This study aims to analyze the acceleration of gravity (g) in free fall with a height of 2 meters using a video tracking application. This research is located in the Department of Geological Engineering, Pattimura University, Ambon. The method used in this research is the experimental method. The tools and materials used in this study were tennis balls (2 grams), baseball (80 grams), roll meter, camera and laptop. Based on the results of data analysis, it was found that the value of gravitational acceleration at a height of 2 meters for samples of tennis balls (2 grams) and baseballs (80 grams) was 9.67 ± 0.27 m/s2 and 9.60 ± 0.27 m/s2.